Policy Coherence and Consistency: An Analysis of the Philippine Foreign Policy towards the West Philippine Sea - S. Rodillas, Ira Lizeth (Policy & Governance Review, 2025)
The territorial dispute in the West Philippine Sea (WPS) has long been a significant threat to the peace and security of not only the Philippines but also of the broader Indo-Pacific region. Despite the emergence of other key global issues, such as the COVID-19 pandemic, tensions in the disputed islands have continued to escalate, compelling the Philippines to pursue various strategies to protect and promote its national interests. This research aims to analyze and compare the consistency and coherence of the foreign policy strategies pursued by the last three administrations, namely the Aquino, Duterte, and Marcos Jr. administrations, with regard to the WPS. It seeks to understand and evaluate the foreign policy of each administration through the lens of both international relations and public policy theories. To produce substantive qualitative research, the author utilized a variety of data sources, including relevant literature, interviews with Philippine diplomats, and official statements by the Presidents. Considering that the Philippines elects a new president every six years and a confluence of factors affect its foreign policy, this paper advocates for a consistent and coherent foreign policy that transcends presidential terms. Given that war is never an option for the country, the President, as the chief architect of Philippine foreign policy, must exhaust all diplomatic measures available to protect and promote the nation's interests.